Theoretical Structural Characterization of XIn2Se4 Ternary Semiconductors Wanted to be Grow Using the Bridgman/Stockbarger Technique - Bekir Gürbulak (Journal of Anatolian Physics and Astronomy)
The importance of semiconductors paving the way for nano and optoelectronic technology has recently been increasing. But, producing them easily and having their vast application fields are most important. For that reason, the crystals have a wide application field and their characteristics which are determined are needed. Some researchers (Irie et al., 1979; Shih et al., 1986) have suggested that the crystals grown should be grown in a single ampoule and a single stage, considering the idea that it would cause selenium loss. Considering this situation, it was decided to grow XIn2Se4 crystal with this method. XIn2Se4 (X=Cu, Mn, Al, Fe) single crystals used in this research were grown using the Bridgman/Stockbarger method. All of the samples were freshly and gently cleaved with a razor blade from the grown ingots and no further polishing and cleaning treatments were required because of the natural mirror-like cleavage faces. The Samples were cleaved along the cleavage planes (001). In this study, single crystal growth was done in a single step. The structure of XIn2Se4 semiconductors was analysed theoretically using x-ray diffractometer (XRD), scanning electron microscopy (SEM), energy dispersive x-ray (EDX) and Raman spectroscopy techniques.